SlZRT2 Encodes a ZIP Family Zn Transporter With Dual Localization in the Ectomycorrhizal Fungus Suillus luteus - Coninx, Laura; Smisdom, Nick; Kohler, Annegret; Arnauts, Natascha; Ameloot, Marcel; Rineau, François; Colpaert, Jan V.; Ruytinx, Joske (Frontiers in Microbiology, 2019)
Ectomycorrhizal (ECM) fungi are important root symbionts of trees, as they can have significant effects on the nutrient status of plants. In polluted environments particular ECM fungi can protect their host tree from Zn toxicity by restricting the transfer of Zn while securing supply of essential nutrients. However, mechanisms and regulation of cellular Zn homeostasis in ECM fungi are largely unknown and it remains unclear how ECM fungi affect the Zn status of their host plants. This study focuses on the characterization of a ZIP (Zrt/IrtT-like protein) transporter, SlZRT2, in the ECM fungus Suillus luteus, a common root symbiont of young pine trees. SlZRT2 is predicted to encode a plasma membrane-located Zn importer. Heterologous expression of SlZRT2 in yeast mutants with impaired Zn uptake resulted in a minor impact on cellular Zn accumulation and growth. The SlZRT2 gene product showed a dual localization and was detected at the plasma membrane and perinuclear region. S. luteus ZIP-family Zn uptake transporters did not show the potential to induce trehalase activity in yeast and to function as Zn sensors. In response to excess environmental Zn, gene expression analysis demonstrated a rapid but minor and transient decrease in SlZRT2 transcript level. In ectomycorrhizal root tips, the gene is upregulated. Whether this regulation is due to limited Zn availability at the fungal-plant interface or to developmental processes is unclear. Altogether, our results suggest a function for SlZRT2 in cellular Zn redistribution from the ER next to a putative role in Zn uptake in S. luteus.